Rainfall Potentials For Crop Crowing in Arid Kutch Region - Singh, R S; Ramakrishna, Y S; Ramakrishna, C S; Bhandari, C S (Annals of Arid Zone, 2016)
The rainfall distribution pattern, crop growing season and their variability in arid Kutch district during 1901-1989 were analysed. The mean duration of growing season in Bhuj area was 9.8 weeks with a large standard deviation of 5.3 weeks. Large deficit of rain water was observed in 16 years, while rain water surplus occured in 23 years. The existing cropping pattern and rain water use efficieney with respect to major crops of the region were analysed and suggestions have been made for improving the crop production potentials of the region.